The Role of Artificial Intelligence in Transforming English Language Learning for Students at Junior High School - Nur Farlina; Ibrahim Manda; Andi Asrifan; Sitti Aisa; Nur Hikmah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This research examines the impact of artificial intelligence (AI) technology, specifically using the Canva application, on English language learning at SMP Negeri 3 Baranti. The study employs a quantitative approach with an experimental design, involving two groups of eighth-grade students: an experimental group using AI-powered Canva for learning activities and a control group following traditional teaching methods. Over an eight-week period, the experimental group engaged with various AI-enhanced educational tools, including learning videos, interactive posters, and quizzes. Data were collected through English skills tests and student questionnaires, and analyzed using descriptive and inferential statistics, including independent t-tests. The findings indicate that students in the experimental group showed significant improvement in their English language skills compared to the control group. Additionally, these students reported higher levels of motivation and engagement in the learning process. The study concludes that integrating AI in educational tools like Canva can enhance the quality of English language education. It recommends that educational institutions consider adopting AI technologies to create a more engaging and effective learning environment. Further research is suggested to explore the long-term effects of AI in education and its adaptation to individual student needs.